Training on Making Soap from Kitchen Herbs in Bancaran Village, Bangkalan Regency - Fitroh Annisaul Mubarokah; Mauliana Silvia; Teguh Setiawan Wibowo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Indonesia is one of the countries with the largest tropical rainforest in the world. This situation causes Indonesia to have the potential to become a country producing herbal ingredients, or spices, which we often encounter in the kitchen. Herbal ingredients are from nature and have many benefits, especially for health. Aside from being consumed, herbs can also be added to products used by the external body, such as herbal soaps. Herbal ingredients in soap can brighten, moisturize, and solve skin problems. The purpose of this community service is to train the community in Bancaran Village regarding making soap from herbal ingredients that are easy to find in the kitchen using simple tools. The methods used are the lecture method and demonstration simulation. The results of the community service show that the people in Bancaran village are very enthusiastic about this training, and the community can make handmade herbal soaps with attractive packaging and then market them.